A Jointly Optimized Variable M-QAM and Power Allocation Scheme for Image Transmission. (29th February 2012) - El-Tarhuni, Mohamed; Hassan, Mohamed; Bin Sediq, Akram
Abstract : We introduce an improved image transmission scheme over wireless channels with flat Rayleigh fading. The proposed scheme jointly optimizes bit power and modulation level to maximize the peak signal-to-noise ratio (PSNR) of the reconstructed image and hence improves the perceptual quality of the received image. In this optimization process, the significance of bits with regard to the overall quality of the image is exploited. The optimality of the proposed algorithm is demonstrated using the Lagrange method and verified through an iterative offline exhaustive search algorithm. For practical implementation, a look-up table is used at the transmitter for assigning the bit power and modulation level to each bit stream according to the received signal-to-noise ratio (SNR) observed at the receiver. The proposed scheme has low complexity since the look-up table is computed offline, only once, and used for any image which makes it suitable for devices with limited processing capability. Analytical and simulation results show that the proposed scheme with jointly optimized bit power and variable modulation level provides an improvement in PSNR of about 10 to 20 dB over fixed power fixed modulation (16-QAM). A further reduction in complexity is achieved by using the average signal-to-noise ratio rather than the instantaneous SNR in selecting the system parameters.